Analysis of the Influence of Internal Factors on Firm Performance: A Systematic Literature Review - Febriyanti, Angela Devi; Nugroho, Bernardus Yuliarto (Dinasti Publisher, 2025)
This study aims to systematically examine the influence of capital structure, liquidity, and profitability on firm value and performance, based on nine scholarly articles published between 2012 and 2024. The method used is a Systematic Literature Review (SLR) with a PRISMA-based approach to select and analyze relevant articles. The synthesis results show that capital structure (measured by DER), liquidity (CR, FDR), and profitability (ROA, ROE, NIM) have varying effects depending on the industrial sector, research period, and geographical context. Capital structure tends to negatively affect firm performance when leverage is excessively high, while profitability generally correlates positively with firm value. Liquidity demonstrates mixed effects—both positive and negative—depending on how it is managed. This study contributes to the development of financial management and industrial engineering by emphasizing the importance of a holistic and data-driven approach in strategic corporate decision-making.